Counterinsurgency Warfare : Theory and Practice - Galula, David; Foreword by A. Nagl (New Delhi Pentagon Press, 2010)
A template for the defeat of insurgents seeks to define the laws of counterinsurgency warfare, discuss its principles, and outline the corresponding strategy and tactics.
Include Index
Keywords: Guerrilla warfare -- Military readiness -- Tactics -- France